Utilizing Linear Regression to Forecast Sales in RD.bag's Online Outlet - Rudi Purnomo; Tutik Khotimah; Ahmad Jazuli (KH. A. Wahab Hasbullah University, 2024)
This research aims to analyze the relationship between various variables and the sales performance of the RD.bag online store using sales data from the period of February 1, 2021, to January 31, 2023. The data collection phase involves retrieving data from Shopee and storing it in an Excel file format. The data is then cleansed of duplicates and irrelevant information in the data cleaning stage, followed by data transformation to tidy up datetime formats and create a dataframe. The analysis is carried out using the linear regression method to observe the relationship between independent and dependent variables. These analysis findings provide insights into the sales performance of the RD.bag online store and can aid in developing more effective marketing strategies. The study also presents suggestions for future research development, including adding variables, exploring advanced analysis methods, and conducting comparative analyses with other online stores in the same industry.